Existential Semantics in Equatives in Japanese and German - Tanaka, Eri; Mizutani, Kenta; Solt, Stephanie (Proceedings of the Amsterdam Colloquium, 2019)
This paper investigates the semantics of two lesser studied equative markers, Japanese hodo and German dermaßen, focusing on accounting for their polarity sensitivity and their presuppositions. We present an analysis according to which these items have weak existential semantics, producing a trivial meaning in certain configurations, and where presuppositional effects derive from competition with the unmodified positive form.